A dialdehyde–diboronate-functionalized AIE luminogen: design, synthesis and application in the detection of hydrogen peroxide. Issue 67 (28th July 2016) - Liu, Guang-Jian; Long, Zi; Lv, Hai-juan; Li, Cui-yun; Xing, Guo-wen
Abstract : A dialdehyde–diboronate-functionalized tetraphenylethene (TPE-DABF) was reported as a H2 O2 -specific AIE luminogen. Abstract : A dialdehyde–diboronate-functionalized tetraphenylethene (TPE-DABF) was reported as a H2 O2 -specific AIE luminogen. TPE-DABF, bearing multiple reductive units (aldehyde, boronate and fructose) in one molecule, afforded an excellent H2 O2 selectivity over other ROS in biological buffer, and can be used for sensitive detection of glucose under neutral conditions.